1997
DOI: 10.1002/(sici)1097-4628(19970822)65:8<1517::aid-app9>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and gelation of poly(vinylidene fluoride) in organic solvents

Abstract: Poly(vinylidene fluoride) (PVdF) converts easily to thermally reversible gel at room temperature in aliphatic ketones or cyclic ketones such as 3-pentanone, 3-hexanone, cyclohexanone, and g-butyrolactone, etc. Gelation of PVdF in these ketones took place through crystallization of polymers from solution. The crystallization process was investigated in detail by Fourier transform infrared (FTIR) measurements. The FTIR spectra were recorded continuously at room temperature until the solution converted to gel. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 0 publications
4
55
0
1
Order By: Relevance
“…10 m • , typical of the crystalline form II of this polymer. 40 The differences in particle shape and crystallinity do not influence the morphologies of the polymer films resulting from binder dissolution and solvent evaporation. Indeed, the spectra of the dry SA and PVdF films obtained after dispersing the binders in H 2 O and NMP, respectively, are almost identical and completely amorphous as shown by the XRD patterns reported in Figure 2c.…”
Section: Resultsmentioning
confidence: 99%
“…10 m • , typical of the crystalline form II of this polymer. 40 The differences in particle shape and crystallinity do not influence the morphologies of the polymer films resulting from binder dissolution and solvent evaporation. Indeed, the spectra of the dry SA and PVdF films obtained after dispersing the binders in H 2 O and NMP, respectively, are almost identical and completely amorphous as shown by the XRD patterns reported in Figure 2c.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, 14 the present authors measured the gelation times (t gel ) of two systems: PVdF/γ-butyrolactone and PVdF/cyclohexanone. In that study, t gel of PVdF in cyclohexanone was found to be smaller than that in γ-butyrolactone.…”
Section: In Situ Ft-ir Spectramentioning
confidence: 99%
“…[9][10][11][12][13] The present authors investigated gelation process of PVdF homopolymer in many organic solvents from measurements of both time-resolved Fourier transform infrared (FT-IR) spectroscopy and dilatometry. [14][15][16][17] Tashiro et al studied the structural change during the gelation process and the resultant aggregation structure of PVdF polymer and solvent molecules in the gel through measurement of the time-resolved FT-IR. 18 Hong and Chou studied the relation between phase separation behavior and gelation kinetics in PVdF/tetra(ethylene glycol) dimethyl ether (TG) solution.…”
mentioning
confidence: 99%
“…In a previous study, we reported our investigation of the gelation process of PVdF in a number of organic solvents without a lithium salt using time-resolved Fourier transform infrared (FT-IR) spectroscopy and dilatometry. [12][13][14][15] In addition, we experimentally estimated the Flory-Huggins interaction parameters (w 12 ) between PVdF and the organic solvents over a wide temperature range using inverse gas chromatography and then clarified the correlation between the thermoreversible gelation of a PVdF solution and the magnitude of w 12 . 16 Here, we report the results of a preliminary study of the gelation process and the structural morphology of a PVdF gel in the presence of a lithium salt, LiBF 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported our investigation of the gelation process of PVdF in a number of organic solvents without a lithium salt using time-resolved Fourier transform infrared (FT-IR) spectroscopy and dilatometry. [12][13][14][15] …”
mentioning
confidence: 99%